2019
DOI: 10.1177/1043659619859049
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Conflicts Between Nurses and Families of a Multi-ethnic Patient Population During Critical Medical Situations in a Hospital

Abstract: Introduction: Little is known about how to avoid intercultural nurse–family conflicts in critical care settings. In this article, strategies are discussed that may be useful to prevent or mitigate intercultural nurse–family conflicts during critical medical situations in hospital. Method: Strategies are based on an ethnographic study by Van Keer et al., other literature, and expert opinion. Results: Sufficient structural measures are needed. First, institutions must create appropriate ward policies, such as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…These problems may result in conflicts between health professionals and family members. Therefore, it is very important to identify family members' needs, to attempt to meet stated needs, and to control their anxiety (10). However, the number of studies on identifying the anxiety and needs of patients' family members is limited.…”
Section: Introductionmentioning
confidence: 99%
“…These problems may result in conflicts between health professionals and family members. Therefore, it is very important to identify family members' needs, to attempt to meet stated needs, and to control their anxiety (10). However, the number of studies on identifying the anxiety and needs of patients' family members is limited.…”
Section: Introductionmentioning
confidence: 99%
“…More and more universities are including nursing content related to cultural competence, culturally congruent health care, and attention to cultural diversity in their undergraduate coursework. There are numerous studies that highlight the importance of such training to avoid prejudices and discriminatory attitudes in new nurses (Nielsen et al, 2019; Plaza Del Pino, 2017; Van Keer et al, 2020), although it may also be necessary to develop other initiatives, not only among students, but also with nurses and other health care professionals, to change these types of attitudes (Noble et al, 2014; Plaza del Pino, 2017). Formal education can have positive effects on the reduction of prejudiced attitudes toward migrants (Easterbrook et al, 2016), although the data available are not conclusive (Civalero et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate those consequences, intercultural coaching of nursing in the workplace can be organized where nurses can appreciate and/or discover new cultural knowledge in the context of their work environment and how to specifically perform nursing tasks in a culturally sensitive manner. Van Keer et al 36 found that “during these sessions, nurses can share their positive and negative experiences of encounters with ethnically diverse families and possible solutions for intercultural communication difficulties can be discussed.” The nurse should ask clients if they have any outstanding cultural, religious, or spiritual factors that staff need to be aware of before, during, and after their care, as variances within a culture exist. For patients who cannot speak, read, or write in the dominant language well, recruitment of nurses with different ethnic background are recommended to help explain information in the language that patients prefer 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Van Keer et al 36 found that “during these sessions, nurses can share their positive and negative experiences of encounters with ethnically diverse families and possible solutions for intercultural communication difficulties can be discussed.” The nurse should ask clients if they have any outstanding cultural, religious, or spiritual factors that staff need to be aware of before, during, and after their care, as variances within a culture exist. For patients who cannot speak, read, or write in the dominant language well, recruitment of nurses with different ethnic background are recommended to help explain information in the language that patients prefer 36 . Nurses from ethnic minority groups can more easily provide inside information to health care professionals from the dominant ethnic group about specific customs or traditions which can affect the care process, and conversely, inform families about regulations in the hospital 36,37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation